Constitutional and administrative law (Contemporary Central & East European Law, 1971)
The following legal acts are discussed in the article:• Law on libraries of April 9, 1968 (Dz. U. 1968 Nr 12, poz. 63);• Law on permissions for public entertaiment and artistic and sport activities of April 9, 1968 (Dz. U. 1968 Nr 12, poz. 64);• Bill on the amendement to the law on repairs and reonstruction, as well as finishing and superstructures of residential houses of July 15, 1968 (Dz. U. 1968 Nr 25, poz. 166);• Law of December 20, 1968 amending the act on higher education (Dz. U. 1968 Nr 46, poz. 334);• Law on building sites in the countryside of April 19, 1969 (Dz. U. 1969 Nr 11, poz. 81).